Bulldaggers, pansies, and chocolate babies : performance, race, and sexuality in the Harlem Renaissance - Wilson, James F. (Triangulations., 2010)
The gay and lesbian presence in black entertainment in Harlem nightclubs, speakeasies, rent parties, and Broadway stages.